2022
DOI: 10.1371/journal.pone.0275852
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of poultry rearing practices and risk factors of H5N1 and H9N2 virus circulating among backyard chickens and ducks in rural communities

Abstract: Background The avian influenza virus (AIV) causes significant economic losses by infecting poultry and occasional spillover to humans. Backyard farms are vulnerable to AIV epidemics due to poor health management and biosecurity practices, threatening rural households’ economic stability and nutrition. We have limited information about the risk factors associated with AIV infection in backyard poultry in Bangladesh. Hence, we conducted a cross-sectional survey comprising epidemiological and anthropological inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…This study investigated the risk factors associated with influenza A, specifically H5 subtype prevalence. The present study detected influenza A viruses in waterfowl, chicken, turkey, and pigeon, similar to previously reported data 34 36 . We screened avian samples and found evidence of H3, H5, and H9 viruses in the tested samples, albeit with specific patterns.…”
Section: Discussionsupporting
confidence: 93%
“…This study investigated the risk factors associated with influenza A, specifically H5 subtype prevalence. The present study detected influenza A viruses in waterfowl, chicken, turkey, and pigeon, similar to previously reported data 34 36 . We screened avian samples and found evidence of H3, H5, and H9 viruses in the tested samples, albeit with specific patterns.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also showed that detecting AIV and A/H5 is higher in sick ducks than in apparently healthy ducks. Previous studies in Bangladesh and other countries have reported similar results for ducks and poultry birds ( 2 , 70–73 ). Even though ducks can secrete large quantities of a deadly virus without manifesting any outward signs of disease, H5N1 can cause the birds to have breathing difficulties such as gaping (mouth breathing), nasal snicking (coughing sound), sneezing, gurgling, or rattling.…”
Section: Discussionsupporting
confidence: 76%
“…AIV is a public health concern in the countries like Bangladesh, where people and poultry are in frequent contact without adequate biosecurity measures in place ( 32 ). LBMs are a significant source of AIV circulation, mutation, and spillover to humans or other wildlife.…”
Section: Discussionmentioning
confidence: 99%
“…As more people turn to LBMs as a source of protein in Bangladesh ( 28 ), robust risk characterization is essential to inform targeted public health interventions at this interface. However, most studies about the risk of AIV biosecurity are conducted in urban areas and communities ( 7 , 29 32 ). The risk of AIV spillover in peri-urban and rural areas remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%